Methodological handbook for analyzing policy coherence: Enhancing synergies and avoiding redundancies - Buritica, Alexander; González, Karen; Rueda, Jorge Armando; Romero, Andrei; Vergara, Daniel; Guevara, Paula; Mideros, María Fernanda; Castro Nunez, Augusto (2025)
The Methodological Handbook for Analyzing Policy Coherence presents a comprehensive framework developed by the Alliance Bioversity & CIAT and the Center for Agrifood Systems Research (Centro ISA) at Universidad de los Andes. This methodological guide provides policymakers, civil society, and international organizations practical tools to assess and improve policy coherence across multiple levels, sectors, and actors. The handbook offers a systematic approach to ensuring that policies not only achieve their intended goals but also align with broader social, economic, and environmental objectives by addressing inconsistencies in the design, implementation, and evaluation of policies.